Selective light olefin synthesis with high ethylene abundance via CO2 hydrogenation over (Ga-In)2O3/SSZ-13 catalysts - Yasemen Kuddusi; Laura Piveteau; Mounir Mensi; Daniel C. Cano-Blanco; Andreas Züttel (Journal of CO2 Utilization)
Direct light olefin synthesis from CO2 hydrogenation is a new pathway to decarbonize the chemical industry. Inspired by the promising catalytic activity of Ga2O3-based catalysts in alkane dehydrogenation, this study reveals that optimizing Ga content in the GaxIn2-xO3/SSZ-13 catalytic system can narrow the product distribution toward light olefins. The optimized catalyst exhibits light olefin and C2H4 selectivity up to 84 % and 45.9 %, respectively, amongst C2+ hydrocarbons with a maximum olefin/paraffin ratio of 6.4 and a CO2 conversion of 14.8 % at 20 bar and 653 K. In particular, a sevenfold increase in C2H4 space-time yield compared to pure metal oxides on SSZ-13 was observed, along with the gradual suppression of C3H8 formation. Herein, we established a catalyst structure-performance relationship as a function of chemical composition. As such, CO and paraffin formation rates can be suppressed, and light olefin formation rates can be enhanced. Therefore, the change in light olefin STY upon gallium incorporation could be ascribed to modulations in the structural and electronic properties, as well as alterations in the surface adsorption and acidic strengths. The findings presented here provide a strategy to tune CO2 hydrogenation product distributions toward specific target products.